Neurobehavioral changes in people with post-stroke aphasia - Edelkraut, Lisa; Moreno-Campos, Lorena; Torres-Prioris, María José; López-Barroso, Diana; Dávila-Arias, María Guadalupe; Berthier-Torres, Marcelo Luis (My University, 2020)
At present, research on neurobehavioral disorders in people with post-stroke aphasia is scarce, especially in Spanish. The objective of this study is to design a new scale on neurobehavioral change, the Scale of Neurobehavioral Affectation in Aphasia (EANA, in Spanish) and to evaluate 14 people affected by chronic post-stroke aphasia (mean age: 51/ DT: 7.2) together with their main informants. At the same time, psychiatric (Neuropsychiatric Inventory, Hospital Anxiety and Depression Scale, Stroke Aphasic Depression Questionnaire), cognitive (Mini Mental State examination, Informer Test) and functional instruments (Stroke and Aphaisa Quality of Life Scale and Barthel Index) have been used to provide a multidimensional description of the affected persons. The results show statistically significant neurobehavioral changes in multiple domains. According to the EANA, those affected with post-stroke aphasia communicate with less frequently, show more introversion, shyness, dependence and apathy, behave in a more infantile manner ("makes me grimaces"), in addition to showing heightened anxiety and impulsivity. Finally, the informants report more aggressive acts, both verbal (insults) and physical (throwing objects, hitting both objects as persons), that did not occur before the stroke. According to the psychiatric instruments, many of the affected cope with anxiety, agitation and apathy, as well as mild depression. At a cognitive level, affected individuals show mild to moderate deficits, especially in working memory and temporal orientation. Functionally most individuals maintain a medium-high level of functional independence in daily activities. These findings support the inclusion of recommendations for the routine assessment and management of neurobehavioral changes to help optimize long-term recovery in people with stroke and aphasia.
Keywords: Afasia; Post-stroke aphasia; Personality; Behavioural disorder